Drought resistance of ten poplar clones in eastern Ukraine - Висоцька, Н. Ю. (Forestry and Forest Melioration, 2023)
Introduction Water deficit as a critical ecological factor is a major limitation for the growth and productivity of trees worldwide. Species of the genus Populus L. are among the most widespread and fast-growing tree species, successfully used in afforestation programs aimed at regrowth of vegetation on degraded and arid lands and reducing desertification. Understanding the mechanisms of drought resistance of various poplar species and hybrids is essential for developing conservation strategies and establishing stands for various purposes in Eastern Ukraine. The aim of our study was to determine the relative drought resistance of 10 poplar clones in Eastern Ukraine. We hypothesized that 1) drought resistance of poplar clones depends on hybridization combinations; 2) clones that are vegetative offspring of trees cultivated in Ukraine since the 1960s are potentially more drought-resistant as they have undergone adaptation to local conditions. Materials and Methods Drought resistance of 10 poplar clones at the age of 7 years, grown in trial plantations in Eastern Ukraine, was determined. The study was conducted under laboratory conditions. The drought resistance of leaf tissues was determined based on changes in water-physical and electrophysiological properties of the leaf apparatus. One-year-old shoots were collected from trees of each clone in five replicates from the middle part of the crown from different sides relative to the cardinal directions. The duration of the rainless period before sample collection was 9 days. Daily maximum air temperatures during 8–15 July ranged from +29.3°C to +33.8°C. To determine statistically significant differences between the mean values of groups during the analysis of variance, the least significant difference (LSD0.05) was calculated. Cluster analysis was used to group clones based on their relative drought resistance similarity. Results The clones 'Perspektyvna' (P. ? euroamericana cv. 'regenerata' ? P. lasiocarpa), 'Lvivska' (P. ? euramericana cv. 'regenerata' ? P. trichocarpa), and 'Nocturne' (P. trichocarpa ? P. lasiocarpa) showed higher resistance to drought. The least drought-tolerant clones were 'Dorskamp' (P. ? euramericana var. Dorskamp) and 'Druzhba' (P. trichocarpa ? P. laurifolia). Conclusions The hypothesis of higher drought resistance in poplar clones cultivated in eastern Ukraine since the 1960s and adapted to local conditions was not confirmed. The hypothesis regarding the dependence of drought resistance on hybrid combinations was also not confirmed. 5 Figs., 2 Tables, 54 Refs.